Electronic Invoice System: The Case of Tabique Engenharia Enterprise - Anabela FERNANDES; Isabel FERREIRA (Communications of International Proceedings, 2021)
All organizations that sell or provide services are required to issue invoices, representing the issuance of thousands of invoices annually. For each invoice issued there is a procedure. Between delivery and receipt of the invoice to the customer, delays or missteps may arise, making the process expensive and time consuming. In order to address these problems, and in compliance with the Community guidelines on e-invoicing, as set out in Directive 2014/55/EU in Portugal, under the e-government strategy, the objective of making the billing process simpler, more efficient and more flexible, the obligation to issue electronic invoices for companies working with public authorities entered into force in January 2021. What are the gains for companies from the adoption of e-invoicing? Through a case study, in a state supplier company, it is intended with this article to present and discuss the process of implementation of electronic invoicing and the associated gains. As a result, it is made known the process of adapting the company in electronic invoicing, to monitor the market in economic and financial information, assisting decision making for the future of the company, improving digital knowledge.
Keywords: E-Government; Electronic Invoices; Case Study.